IMPROVING THE RELIABILITY OF THREE PHASE INVERTER BASE ON CUK CONVERTER FOR PV APPLICATION - Vinayak Bhagwan Kashid; Prof.H.T.Jadhav (International Journal of Innovations in Engineering Research and Technology, 2021)
This paper present three phase inverter base on the cuk converter. The prime foredeal of this proposed theory is energy storage element like as inductors and capacitors can be reduced in order to reforms the system reliability and reduced total size alike total cost of system. The uncommon characteristics of cuk converter, when required ac voltage is depress or greater than dc side voltage but this quality is not found in conventional Current source inverter as well as voltage source inverter. Traditional method required any mathematical model but the fuzzy controller does not require any mathematical model and it’s very simple to implement. The cuk converter is simulated for grid and their output voltage is settling at desired voltage. The performance of cuk converter simulated by using MATLAB/SIMULINK and contrast study is performed.